Conspirituality in COVID-19 Times A Mixed-method Study of Anti-vaccine Movements in Spain - Griera, Maria del Mar 1978-; Gras, Jordi Morales i; Clot-Garrell, Anna; Cazarin, Rafael (2022)
This article focuses on the development of COVID-19 anti-vaccination movements in Spain and explores their relationship with the phenomenon of conspirituality. By using a mixed-methods approach combining big data analysis with small ethnographic data analysis, we examine how conspiracy theories and spiritual ideas circulate, merge and crystallize in particular practices and encounters in Spain. The big data analysis of Twitter conversations reveals the centrality and hypervisibility of far-right populist influencers, and the predominance of classic conspiracy views over spiritual ones in anti-vax discourses. However, ethnographic observations and the analysis of digital ethnographic data of other social media platforms (Facebook, YouTube and Telegram) show the emergence and growth of a network of actors merging spiritual messages, alternative visions on health and healing, anti-vax views and conspiracy theories in different ways and degrees. These are the conspiritual assemblages, which are smaller and more local in their scale and impact but still significant in sociological terms.
Keywords: Anti-vaxx; Spain; Spirituality; Vaccination; Conspirituality